Detection Accuracy of High-Resolution Infrared Satellite Precipitation Estimates Over Mainland China: A Multiperspective Assessment of Fengyun-4A - Da Qian; Yi Lyu; Zhehui Shen; Hao Wu; Ruochen Huang; Bin Yong; Hongjun Su (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Infrared satellite observations are most widely used for precipitation estimation due to high spatial-temporal resolution and short latency, especially suitable for real-time hydrological applications such as flood forecasting and drought monitoring. The Fengyun-4A (FY4A) satellite, as part of China's new generation of meteorological satellites, has been providing two official infrared-based satellite precipitation estimates, i.e., FY4A-REGC (near-real-time, covering the Chinese region) and FY4A-DISK (post-real-time, covering the Asia–Pacific region). Despite integrated into operational systems such as hydrologic forecasting, their error characteristics and correction potentials remain unexplored. This study comprehensively analyzed the detection accuracy and the performance in capturing precipitation characteristics (i.e., the precipitation amount, frequency, intensity, and diurnal cycle variability) of four precipitation products (i.e., FY4A-REGC versus PERSIANN-CCS and FY4A-DISK versus PDIR-Now) over the mainland China for more than one whole year. The results show that FY4A-DISK achieves the best detection capability, whereas PDIR-Now excels in accurately reproducing precipitation characteristics. Meanwhile, benefiting from its high-frequency observations over the Chinese region, FY4A-REGC consistently outperforms PERSIANN-CCS. Further investigation shows that two FY4A products demonstrate better detection capability in high-altitude regions, although they are less sensitive to high-intensity precipitation events. Interestingly, FY4A-REGC shows good agreement with rain gauge observations, whereas FY4A-DISK performs poorly when comparing the diurnal cycle of precipitation. This can be attributed to the discontinuity and mismatch of the observation window for the onboard sensor. These findings offer insights to improve the retrieval quality and operational application of the Fengyun-4 precipitation products.